Double-target neural circuit-magnetic stimulation improves motor function in spinal cord injury by attenuating astrocyte activation - Dan Zhao; Ye Zhang; Ya Zheng; Xu-Tong Li; Cheng-Cheng Sun; Qi Yang; Qing Xie; Dong-Sheng Xu (Neural Regeneration Research, 2023)
Multi-target neural circuit-magnetic stimulation has been clinically shown to improve rehabilitation of lower limb motor function after spinal cord injury. However, the precise underlying mechanism remains unclear. In this study, we performed double-target neural circuit-magnetic stimulation on the left motor cortex and bilateral L5 nerve root for 3 successive weeks in a rat model of incomplete spinal cord injury caused by compression at T10. Results showed that in the injured spinal cord, the expression of the astrocyte marker glial fibrillary acidic protein and inflammatory factors interleukin 1β, interleukin-6, and tumor necrosis factor-α had decreased, whereas that of neuronal survival marker microtubule-associated protein 2 and synaptic plasticity markers postsynaptic densification protein 95 and synaptophysin protein had increased. Additionally, neural signaling of the descending corticospinal tract was markedly improved and rat locomotor function recovered significantly. These findings suggest that double-target neural circuit-magnetic stimulation improves rat motor function by attenuating astrocyte activation, thus providing a theoretical basis for application of double-target neural circuit-magnetic stimulation in the clinical treatment of spinal cord injury.